Impact of the 2014 American Academy of Pediatrics recommendation and of the resulting limited financial coverage by the Italian Medicines Agency for palivizumab prophylaxis on the RSV-associated hospitalizations in preterm infants during the 2016-2017 epidemic season: a systematic review of seven Italian reports - Renato Cutrera; Andrea Wolfler; Simonetta Picone; Giovanni A. Rossi; Giuliana Gualberti; Rocco Merolla; Antonio Del Vecchio; Alberto Villani; Fabio Midulla; Andrea Dotta (BMC, 2019)
Abstract Background The only pharmacologic prophylaxis against respiratory syncytial virus (RSV) infection in preterm infants is the humanized monoclonal antibody palivizumab. After the 2014 modification of the American Academy of Pediatrics (AAP) recommendations, the Italian Medicines Agency (AIFA) limited the financial coverage for palivizumab prescriptions to otherwise healthy preterm infants with < 29 weeks of gestational age (wGA) aged < 12 months at the beginning of the 2016-2017 RSV season. However, due to the effect on disease severity and hospitalizations following this limitation, shown by several Italian clinical studies, in November 2017 AIFA reinstated the financial coverage for these infants. In this systematic review, we critically summarize the data that show the importance of palivizumab prophylaxis. Methods Data from six Italian pediatric institutes and the Italian Network of Pediatric Intensive Care Units (TIPNet) were retrieved from the literature and considered. The epidemiologic information for infants 29-36 wGA, aged < 12 months and admitted for viral-induced acute lower respiratory tract infection were retrospectively reviewed. RSV-associated hospitalizations were compared between the season with running limitation, i.e. 2016-2017, versus 2 seasons before (2014-2015 and 2015-2016) and one season after (2017-2018) the AIFA limitation. Results During the 2016-2017 RSV epidemic season, when the AIFA limited the financial coverage of palivizumab prophylaxis based on the 2014 AAP recommendation, the study reports on a higher incidences of RSV bronchiolitis and greater respiratory function impairment. During this season, we also found an increase in hospitalizations and admissions to the Pediatric Intensive Care Units and longer hospital stays, incurring higher healthcare costs. During the 2016-2017 epidemic season, an overall increase in the number of RSV bronchiolitis cases was also observed in infants born full term, suggesting that the decreased prophylaxis in preterm infants may have caused a wider infection diffusion in groups of infants not considered to be at risk. Conclusions The Italian results support the use of palivizumab prophylaxis for otherwise healthy preterm (29-36 wGA) infants aged < 6 months at the beginning of the RSV season.